Every secret thing eaudiobook - Lippman, Laura (Recorded Books Inc., 2009)
One of mystery writing's most acclaimed novelists for her brilliant Tess Monaghan series, Laura Lippman won the Anthony and Barry Awards for this riveting stand-alone. Kicked out of a birthday party, 11-year-olds Alice and Ronnie walk home and encounter a baby left in a carriage. Their earnest desire to do a good deed ends tragically, however, and seven years later they are released from "kid prison" to start their lives anew..